Pendampingan Pengasuh dalam Peningkatan Perkembangan Anak - Fandy Yoduke; Novy Helena Catharina Daulima; Mustikasari Mustikasari (NHM PRESS, 2023)
This paper aims to report on the improvement in the development of preschool-age children carried out in children aged 3.6 years. The design used in this writing is qualitative descriptive with a healthy single-case approach in a family setting. Mental nursing care interventions with a diagnosis of readiness to improve the development of preschool-age children through mentoring provide new experiences for children and increase child development maturity and provide new experiences for caregivers in accompanying the child's growth and development process. Furthermore, it is necessary to reexamine the interacting factors in the development of preschool-age children.